EFFECT OF ROAD BITUMEN MODIFICATION WITH NANOCARBON POWDER - Zhurinov M.Zh.; Teltayev B.B.; Kalybay A.A. (Academic Journal of Physical and Chemical Sciences, 2020)
Low temperature characteristics (stiffness and m-value) have been determined on a bending beam rheometer in the paper for a road bitumen of grade BND 70/100 and the same bitumen with adding of a nanocarbon powder in the quantity of 2% by weight. The bitumen has been produced by Pavlodar petrochemical plant (Kazakhstan) from a crude oil of Western Siberia (Russia) by direct oxidation. The bitumen has the following standard characteristics: penetration depth of the needle (penetration) at 25°С: 75 dmm; ductility at 25°С: 118 cm; softening point: 47.5°С; Fraas point: -28.5°С. The nanocarbon powder with sizes of 150-200 nm has been obtained from a coal of the “Saryadyr” deposit (Akmola region, Kazakhstan). A mechanical dispergator has been used for dispersing of the coal with sizes up to 50 mm (till 2-3 mm), an aerodynamic mill (till 20 µm) and a reactor with rotating electromagnetic field. Content of carbon and ash in the nanopowder is 92.74% and 2.16% respectively. Average moisture of the nanopowder is 2%. Before testing on the bending beam rheometer the neat bitumen and the nanocarbon bitumen have passed double artificial aging: short-term aging under standard AASHTO T 240-13 and long-term aging under standard ASTM D 6521-08 [14]. It is found out that addition of the nanocarbon powder improves low temperature resistance of the bitumen. The effect of the bitumen modification with the nanocarbon powder is the highest one at very low temperatures. The possibility has been shown for the use of the bitumen of grade BND 70/100 (of more viscous consistence) at its modification with the nanopowder both in the southern regions of the republic and in the northern ones.